2002
DOI: 10.1046/j.1365-2044.2002.02902_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia following knee arthroscopy: an assessment of intra‐articular neostigmine

Abstract: Intra-articular local anaesthetic agents have been shown to reduce postoperative requirements and pain scores following knee arthroscopy [1]. It has been shown that intra-articular administration of the acetylcholinesterase inhibitor neostigmine at a dose of 0.5 mg also has an analgesic effect [2]. In this prospective, randomised, double-blind study we compared the quality and duration of postoperative analgesia provided by intra-articular neostigmine alone and in combination with intra-articular ropivacaine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…8,9 However, other investigators have shown no benefit of peripherally applied neostigmine. 10,11 A recent study that added neostigmine 500 g or placebo to prilocaine 3 mg/kg in IVRA showed reduction in sensory and motor block onset time and prolongation of time to first analgesic request in the neostigmine group. 12 In this study, we hypothesized that peripheral application of neostigmine 1 mg added to lidocaine for IVRA would prolong postoperative analgesia and reduce analgesic requirement without significant adverse effect.…”
mentioning
confidence: 99%
“…8,9 However, other investigators have shown no benefit of peripherally applied neostigmine. 10,11 A recent study that added neostigmine 500 g or placebo to prilocaine 3 mg/kg in IVRA showed reduction in sensory and motor block onset time and prolongation of time to first analgesic request in the neostigmine group. 12 In this study, we hypothesized that peripheral application of neostigmine 1 mg added to lidocaine for IVRA would prolong postoperative analgesia and reduce analgesic requirement without significant adverse effect.…”
mentioning
confidence: 99%